Perception of COVID-19 Impact on Canadian Occupational Therapy Curricula: Academic and Fieldwork. (June 2023) - MacKenzie, Diane; Martini, Rose; Roduta Roberts, Mary; Campbell-Rempel, Margaret Anne; Ausman, Christine
Background. Delivery of occupational therapy education programs in Canada faced significant disruptions and adaptations because of the COVID-19 pandemic. Curriculum changes were made rapidly under extreme conditions.Purpose. To document and explore changes to curricula (academic and fieldwork), instructional, and assessment methods implemented by Canadian occupational therapy programs in response to the pandemic and capture their perceived impact on student learning.Method. This convergent mixed method design study employed a cross-sectional descriptive survey followed by a member check focus group. Participant recruitment targeted Canadian occupational therapy university program directors, curriculum chairs, and fieldwork coordinators.Findings. Results highlight curriculum modifications included shifting from in-person to online delivery and re-sequencing or deferring in-person components. Fieldwork placements were similarly affected and included adoption of simulations and telepractice.Implications. The development of interpersonal "soft skills" are perceived as being the most disrupted, but the impact of student learning on actual practice is not yet known.